2021
DOI: 10.1111/1744-9987.13663
|View full text |Cite
|
Sign up to set email alerts
|

Performance, clinical effectiveness, and safety of immunoadsorption in a wide range of indications

Abstract: Immunoadsorption is well known to selectively remove immunoglobulins and immune complexes from plasma and is applied in a variety of autoimmune diseases and for desensitization before, or at acute rejection after organ transplantation. Performance, safety, and clinical effectiveness of immunoadsorption were the aim of this study. This prospective, noninterventional, multicentre cohort study included patients treated with immunoadsorption (Immunosorba or GLOBAFFIN adsorbers) for any indication. Clinical effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Second, we demonstrated that IgG apheresis decreased the SARS-CoV-2 IgG S antibody levels by about 64% per treatment session. This is comparable with the total IgG reduction per treatment and according to results reported by others ( 19 ). However, due to the lower detection limits of our laboratory we could not exactly calculate total IgG decrease.…”
Section: Discussionsupporting
confidence: 93%
“…Second, we demonstrated that IgG apheresis decreased the SARS-CoV-2 IgG S antibody levels by about 64% per treatment session. This is comparable with the total IgG reduction per treatment and according to results reported by others ( 19 ). However, due to the lower detection limits of our laboratory we could not exactly calculate total IgG decrease.…”
Section: Discussionsupporting
confidence: 93%
“…As revealed by symptom remission and improved mRS scores, the patients responded well to treatment and their symptoms improved. What's more, immunoadsorption (IA) is a potential method of apheresis that selectively removes immunoglobulins while preserving other plasma proteins [14]. It may be considered as a treatment option for anti-DPPX encephalitis since the anti-DPPX antibodies are predominantly comprised of IgG1 and IgG4 [8], however, further research is necessary to determine its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no specialized therapies for anti-DPPX encephalitis, but immunotherapy is commonly used and has potential benefits for most patients [2,12]. The efficacy of plasma exchange, a first-line therapy for anti-NMDA receptor encephalitis, remains unclear for patients with anti-DPPX encephalitist [13,14]. Further investigations are needed to better understand this disease and develop effective treatments.…”
mentioning
confidence: 99%
“…To date, immunotherapy with chimeric anti-CD20 monoclonal antibody (Rituximab) has demonstrated some efficacy by offering a potentially safe and effective treatment ( Green et al, 2019 ). The same is true for removal of antibodies through regular plasmapheresis, immunoadsorption ( Fuchs et al, 2022 ) or possibly proteasome inhibition ( Alishetti et al, 2020 ) that could be methods to reduce the risk of allograft failure.…”
Section: Discussionmentioning
confidence: 99%